Enhancing city authenticity through humanitarian architecture: A synergy of design and identity, case study, Al-Diriyah, Saudi Arabia - Rahmayati, Yenny; AlGhunaim, Jory (Institute for Advanced Science Social, and Sustainable Future, 2024)
Architecture acts as a facade to the world, in which one can understand the insides of the people, religion, culture, and much more about a city. Using humanitarian architecture as a guide for reconstructing, as well as the long-term impacts of the urban planning of a city in terms of sustainability and authenticity, this study answers the questions of how the City's character and identity can be maintained while providing quick assistance via humanitarian architecture. What are the challenges that prevent humanitarian architecture from enhancing cities' authenticity, and how can we overcome them? By examining Al-Diriyah project, this study aims to look into the complex relationship of humanitarian architecture with the branding and authenticity of Riyadh, Saudi Arabia from the perspective of residents and non-residents. A blended qualitative and quantitive approach was applied as a comprehensive methodology to achieve the objectives. This study will help the application of humanitarian architecture for rebuilding countries in the East, highlighting authenticity and maintaining its cultural significance.